JOB DEMANDS & TURNOVER INTENTION: CHANGES IN WORK SITUATION DURING THE COVID-19 PANDEMIC - Cindy Jacop; Zamralita Zamralita; Tetty Rismiyati; Achmad Khalid Alfajar Ardjuna (State Islamic University (UIN) Ar-Raniry, 2023)
The prolonged pandemic caused Job Demands at Company X to increase due to the shift in working conditions to WFH which led to the emergence of Turnover Intention. Job Demands are the physical, psychological, social and organizational aspects of work that have an impact on physical or psychological aspects (Bakker and Demerouti, 2007), while Turnover Intention is the probability that someone will leave the organization in the near future (Jackson S. & Jackson L., 2019). This study uses the Stress Appraisal Theory by Richard Lazarus (Baumeister & Vohs, 2007), uses an explanatory quantitative approach with a survey method with 50 participants. The results showed that Job Demands had a significant effect on Turnover Intention (p=0.012), and only one dimension of Job Demands, namely Role Conflict, which shows a significant effect on Turnover Intention, which is equal to p=0,291. Referring to the questions and research objectives, the conclusion is that the increase in Job Demands had a significant effect on the Turnover Intention of Company X employees during the pandemic.